Pengaruh Electronic Word of Mouth dan Perceived Ease of Use Terhadap Keputusan Pembelian Video Game pada Platform Steam - Pratama, Lalu Nadra Ananda; Rusminah, Rusminah (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2024)
This study aims to examine the influence of Electronic Word of Mouth (eWOM) and Perceived Ease of Use (PEU) on the purchase decision of video games on the Steam platform. The population of this study is all consumers on the Steam platform in Mataram City, while the sample of this study is 100 consumers on the Steam platform using purposive sampling. This type of research is an associative research. Data processing in this study uses SPSS 25.0 for Windows, where validity tests, reliability tests, classical assumption tests, path analysis tests, significance tests (t tests), and coefficient of determination tests (R2). Based on the results of the analysis, all variables have a partial effect, where eWOM has an effect on the purchase decision, and PEU has an effect on the purchase decision. Based on these results, it is recommended that Steam improve the quality of eWOM and PEU, resulting in an increase in the purchase decision of video games on the Steam platform